E-agriculture and e-government for global policy development : implications and future directions - Maumbe, Blessing M., 1966- (Hershey, PA : Information Science Reference, 2010)
'This book provides critical research and knowledge on electronic cultivation and political development experiences from around the world'--Provided by publisher.
Awareness and the use of mobile phones for market linkage by smallholder farmers in Kenya -- E-agriculture development in South Africa : opportunities, challenges and prospects -- Agriculture, communication, and socioeconomic development : a proposal for e-agriculture in Nigeria -- Newly emerging e-commerce initiatives on the agricultural market in Poland -- The development of e-agriculture in sub-Saharan Africa : key considerations, challenges, and policy implications -- Diffusion and dissemination of agricultural knowledge : an e-communication model for rural India -- Using ICT to resolve the modernization paradox for rural communities in Africa : a theoretical exploration and conceptualization -- Connected government for a developing country context : an assessment of the extent of inter-departmental integration for selected government departments in Zimbabwe -- Zambia and e-government : an assessment and recommendations -- Globalized workforce development and responsible global citizenship through e-literacy capacity building programs for low income African countries -- Building capacity for electronic governance in developing countries : critical success factors -- The use of information and communication technologies for health service delivery in Namibia : perceptions, technology choices, and policy implications for sub-Saharan Africa -- ICTs as tools for poverty reduction : the Tanzanian experience -- Impact of e-government implementation on poverty reduction in rural India : selected case studies -- The development of an organic agriculture model : a system dynamics approach to support decision-making processes -- Role of telecommunications in precision agriculture -- World wide weber : formalise, normalise, rationalise : e-government for welfare state - perspectives from South Africa.
Includes bibliographical references and index.
Keywords: Electronic commerce; Internet in agriculture; Internet in public administration; Globalization